Implementation of Land Auction for Kebonharjo Village: A Comparative Perspective - Teddy Satrio Wicaksono; Marisa Kurnianingsih; Arief Budiono (Audito Comparative Law Journal (ACLJ), 2023)
The purpose of this research is to find out the procedure for village treasury land lease agreements through an auction system and to find out the obstacles encountered in the auction process for village treasury land in Kebonharjo, Polanharjo District, Klaten Regency. This study uses an empirical approach method. The type of research used in this research is descriptive analysis with a comparative approach perspective. The results of this study concluded that the procedures for land lease agreements for treasury village in Kebonharjo Village, Polanharjo District, Klaten Regency were carried out through several stages, namely: (1) Forming an auction committee (2) Collecting data on village treasury land, (3) Disseminating information regarding the existence of village treasury land auction. (4) Informing the auction rules, (5) Selecting the auction winner, and (6) Entering into a village treasury land lease agreement. The obstacle in the process of implementing the village treasury land auction held by the government of Kebonharjo Village, Polanharjo District, Klaten Regency, was the lack of interest from the community who took part in and attended the auction being held. This is because most people already have privately cultivated land and not all work as farmers. So that not all residents want to participate and attend the auction held.